Effectiveness of two weeks of high-intensity interval training on performance and hormone status in adolescent triathletes - Lee, C. L.; Hsu, M. C.; Astorino, T. A.; Liu, T. W.; Chang, W. D. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Weekly training volumes for triathlete are typically higher and may cause fatigue and musculoskeletal injury risk. High-intensity interval training (HIT) is a potent time-efficient strategy to induce adaptations normally associated with traditional endurance training. Therefore, the aim of this study was to investigate the effect of two weeks of in-season HIT on exercise capacity and hormonal responses in young triathletes.